Perspective: Did Covid-19 Change Non-small Cell Lung Cancer Surgery Approach? - Ciriaco, Paola; Carretta, Angelo; Bandiera, Alessandro; Muriana, Piergiorgio; Negri, Giampiero (Frontiers in Surgery, 2021)
The novel coronavirus (Covid-19), as of January 2021, infected more than 85 million people worldwide, causing the death of about 1,840 million. Italy had more than 2 million infected and about 75,000 deaths. Many hospitals reduced their ordinary activity by up to 80%, to leave healthcare staff, wards, and intensive care unit (ICU) beds available for the significant number of Covid-19 patients. All this resulted in a prolonged wait for hospitalization of all other patients, including those with non-small cell lung cancer (NSCLC) eligible for surgery. The majority of thoracic surgery departments changed the clinical-therapeutic path of patients, re-adapting procedures based on the needs dictated by the pandemic while not delaying the necessary treatment. The establishment of Covid-19-free hub centers allowed some elective surgery in NSCLC patients but most of the operations were delayed. The technology has partly facilitated patients’ visits through telemedicine when security protocols have prevented face-to-face assessments. Multidisciplinary consultations had to deal also with the priority of the NSCLC cases discussed. Interpretation of radiologic exams had to take into account the differential diagnosis with Covid-19 infection. All the knowledge and experience of the past months reveal that the Covid-19 pandemic has not substantially changed the indications and type of surgical treatment in NSCLC. However, the diagnostic process has become more complex, requiring rigorous planning, thus changing the approach with the patients.